Climate instability and international migration - Mathilde Maurel; Michele Tuccio (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
The importance of international migration for its economic and social implications is nowadays widely acknowledged both in the academic literature and advocacy reports. Recently the debate has stimulated the inclusion of environmental factors into the possible explanations of migration, in order to account for the specificity of south-south migration. To assess the indirect linkages between climate change, agricultural share over GDP and migration, this study exploits an instrumental variable approach, using data for 108 countries for the period 1960-2000. Our model emphasises that anomalies in temperature and rainfalls accelerate the urbanization process, implying a decline in the agricultural share in the GDP. Within-borders migration from rural to urban area leads workers to engage in cross-border migration. We find that cross-border migration induced by a two standard deviation increase in precipitation (temperature) anomalies represents up to 8% (4%) of total migration.
Keywords: F22; J61; O15; Q54; 330